Impelementasi Manajemen Pendidikan Karakter Peserta Didik di Madrasah (Studi Analisis Kepemimpinan Kepala Madrasah MI NW Tangar Lingsar) - Pashurrahman; Ahmad Zikrul Umam; Saprudin Efendi3 (Pendidikan Al-Gafari, 2024)
Education is an effort or effort made by educators to develop and maintain students' potential, in the mentoring process which includes characters such as morals, morals, ethics, manners, and other knowledge. This research was conducted with the following objectives: 1) To find out the strategy of the madrasa head in implementing management of student character education at MI NW Tangar Lingsar, 2) To find out the internal and external environmental conditions of student character education at MI NW Tangar Lingsar, 3) To find out the factors obstacles to implementing student character education management at MI NW Tangar Lingsar and knowing the solution. The object of this research is in the classroom or outside the school and the subject of this research is aimed at madrasah heads, teachers, guidance and counseling teachers, students, parents/community, and all educators and educational staff within the scope of the school environment at MI NW Tangar Lingsar. The results of this research show that MI NW Tangar Lingsar has been able to carry out and implement character education management quite well, this can be seen when students and teachers are outside the school or inside the school. Where some students are used to implementing good character towards others, teachers always supervise and are responsible for forming the students' character.